Peran Orang Tua Asuh Terhadap Literasi Digital Anak di Pondok Kasih Bali - Santi, Ni Kadek Ferlin Julia; Ginting, Richard Togaranta; haryanti, Ni Putu premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
ABSTRACT Information literacy is generally interpreted as a standard and reference for recognizing when information is needed and the ability to find, search, analyze, evaluate and communicate information. Mastery of information plays an important role because technology and information are so easily accessible and used anytime and anywhere. The purpose of this study was to determine parents' understanding of digital literacy and whether foster children are proficient in digital literacy. This research was conducted using a qualitative approach with descriptive methods by collecting data from observations, interviews, and documentation. This study discusses the role of foster parents in children's digital literacy at Pondok Kasih Bali. The population of this research is foster parents. The results of this study indicate that children in Pondok Kasih Bali carry out digital literacy activities but are still not effective due to several obstacles such as inadequate facilities, for the role of foster parents in Pondok Kasih Bali they also play an important role in children's curiosity - pretty tall kid.   Keywords : digital literacy, information literacy, the role of parents